The Sustainable Links of Development between Leadership and Organizational Cultures - Asadi, Rahil; Stefanescu, Dumitru (Journal of Economic Development, Environment and People, 2019)
Leadership performances develops closely connected to the institutional behaviour and societal culture given the permanent trends to implement changes to update standards according to existing norms and rigors existing in any company. The styles adopted in managing or leading the activities influences the tasks’ achievement, the future path to take and the way success is understood, accepted, shared and disseminated. Nowadays, companies face compulsory the influences of more cultures, given the temptation of delocalisation, the curiosity of working with immigrants, the advantages provided in different situations of accepting a higher exposure of leader to different sides of performance, different dimensions of market and financial profits, new behaviours in managing the employees. Starting from this idea, the purpose of this study is to identify and enquire into the hidden dimensions of organizational culture and how the leadership style impacts the strategic developing and let effective relations spring out. The research is built on a survey based on designed questioner applied to 550 leaders and employees, members of the operation and Maintenance Company of MAPNA (Q&M) in Iran. Data collected refers to MLQ leadership style and Denison's Organizational Culture Questionnaire, and the responses received were analysed with SPSS and Smart Plus software. The findings reveal that the relationship between the leadership style and the organizational culture are strongly linked to each other. Therefore, those leaders able to change and accept to use a transformational style will assist the company to move forward faster that those who adopt and keep the transactional style as the single one to prove important.